2017
DOI: 10.18794/aams/69141
|View full text |Cite
|
Sign up to set email alerts
|

Gait analysis in children after the lengthening of the lower limb by the Ilizarov technique

Abstract: WstępOsteogeneza dystrakcyjna, jako metoda leczenia zaburzeń osi i skrótów kończyn dolnych, jest procesem długotrwałym, co niekorzystnie wpływa na stan funkcjonalny narządu ruchu oraz psychikę dziecka. W związku z powyższym celem pracy była analiza parametrów czasoprzestrzennych chodu oraz porównanie wyników leczenia u dzieci po wydłużeniu goleni i uda metodą Ilizarowa.Materiał i metodyBadania wykonano u 40 dzieci z asymetrią kończyn dolnych leczonych w Katedrze i Oddziale Klinicznym Ortopedii w Sosnowcu w lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Research data published on the subject of gait analysis for amputees above the knee (trans-femoral amputation) (13,14,15), or gait analysis for patients treated with an Ilizarov technique (6,16), while reports concerning with gait analysis for patients treated by using an Ilizarov external and they have amputation are relatively very scarce. This study dealing with the effect Ilizarov on phases of gait cycle by comparing between two stages (pre-operation and post-operation Ilizarov).…”
Section: Resultsmentioning
confidence: 99%
“…Research data published on the subject of gait analysis for amputees above the knee (trans-femoral amputation) (13,14,15), or gait analysis for patients treated with an Ilizarov technique (6,16), while reports concerning with gait analysis for patients treated by using an Ilizarov external and they have amputation are relatively very scarce. This study dealing with the effect Ilizarov on phases of gait cycle by comparing between two stages (pre-operation and post-operation Ilizarov).…”
Section: Resultsmentioning
confidence: 99%
“…This means the patients depend (leaning) on a non-operated limb more than operated limb to compensate asymmetry of gait. Previous literature identified the stance phase in the operated on the limb was shorter than in the non-operated on the limb, whilst the swing phase in the operated on the limb was longer than in the nonoperated on the limb in children with leg length discrepancy [23,24]. Also, the study demonstrated that the double support duration of the operated limb with Ilizarov was higher and no significant difference compared to without Ilizarov, whilst the double support duration of the non-operated limb with Ilizarov was a higher and significant difference compared to without Ilizarov.…”
Section: Discussionmentioning
confidence: 99%